The Role of 3D-pCASL MRI in the Differential Diagnosis of Glioblastoma and Brain Metastases - Solozhentseva, Kristina; Batalov, Artem; Zakharova, Natalia; Goryaynov, Sergey; Pogosbekyan, Eduard; Pronin, Igor (Frontiers in Oncology, 2022)
Purpose: The aim of this study was to determine the possibility to differentiate between glioblastoma and brain metastases using intrаtumoral and peritumoral cerebral blood flow measured by 3D pCASL (pseudocontinious arterial spin labeling) MRI-perfusion. The second aim of this study was to determine significance of pCASL in differential diagnosis in distinguishing histological subgroups of brain metastases. Materials and methods: This study included 173 patients aged 12 to 83 years (median age - 61 years), who were observed at the National Medical Research. All patients received preoperative MRI with pCASL perfusion. After that all patients were operated and received histological diagnosis. Results: In this study we discovered that intratumoral cerebral blood flow in brain metastases and glioblastoma measured by pCASL have statistically significant difference (p<0,05), however demonstrate insufficiently low specificity and sensitivity. Peritumoral blood flow showed higher specificity and sensitivity in differential diagnosis between these two diseases. Regarding pCASL and different histological groups our study showed statistically significant differences between lung and melanoma metastases and lung and kidney metastases. Conclusions: pCASL could be used in differential diagnosis between glioblastoma and brain metastases. Measurement of peritumoral blood flow demonstrate higher specificity and sensitivity then intratumoral blood flow. In addition, pCASL demonstrate the ability to distinguish lung metastases from kidney and melanoma metastases.